2018
DOI: 10.1038/s41467-018-05025-7
|View full text |Cite
|
Sign up to set email alerts
|

Ternary complex of Kif2A-bound tandem tubulin heterodimers represents a kinesin-13-mediated microtubule depolymerization reaction intermediate

Abstract: Kinesin-13 proteins are major microtubule (MT) regulatory factors that catalyze removal of tubulin subunits from MT ends. The class-specific “neck” and loop 2 regions of these motors are required for MT depolymerization, but their contributing roles are still unresolved because their interactions with MT ends have not been observed directly. Here we report the crystal structure of a catalytically active kinesin-13 monomer (Kif2A) in complex with two bent αβ-tubulin heterodimers in a head-to-tail array, providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 69 publications
6
73
0
Order By: Relevance
“…Our results showed that GTP hydrolysis required the associated tubulin dimers to be released from AMP-PNP-bound KIF2A-NM (i.e. bound only with DARPin, which disrupts the 1:2 KIF2A:tubulin dimer complex, as previously shown [49]). This suggests that the bending of tubulin dimers by KIF2A-NM per se does not trigger GTP hydrolysis; instead it is the return of free tubulin dimers to their native conformation that promotes the activity.…”
Section: Tubulin-gtp Hydrolysis Can Be Triggered By Binding and Unbinsupporting
confidence: 83%
See 4 more Smart Citations
“…Our results showed that GTP hydrolysis required the associated tubulin dimers to be released from AMP-PNP-bound KIF2A-NM (i.e. bound only with DARPin, which disrupts the 1:2 KIF2A:tubulin dimer complex, as previously shown [49]). This suggests that the bending of tubulin dimers by KIF2A-NM per se does not trigger GTP hydrolysis; instead it is the return of free tubulin dimers to their native conformation that promotes the activity.…”
Section: Tubulin-gtp Hydrolysis Can Be Triggered By Binding and Unbinsupporting
confidence: 83%
“…However, their depolymerizing function only happens at the ends of MTs, where they use the energy derived from ATP hydrolysis to dissociate tubulin dimers [47,48]. Our structural study shows each kinesin-13 monomer can bind to two tubulin dimers in tandem and bend both the intra-and inter-dimer curvature [49]. We postulate that this extreme bending of tubulin dimers by kinesin-13 ultimately leads to their dissociations from protofilament ends.…”
Section: Gtp Cap and Mt Stabilitymentioning
confidence: 75%
See 3 more Smart Citations